2014
DOI: 10.1002/mrd.22320
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin regulates the expression of aquaporin 5 in the late‐pregnant rat uterus

Abstract: SUMMARYAquaporins (AQPs) are integral membrane channels responsible for the transport of water across a cell membrane. Based on reports that AQPs are present and accumulate in the female reproductive tract late in pregnancy, our aim was to study the expression of AQP isoforms (AQP1, 2, 3, 5, 8, and 9) at the end of pregnancy in rat in order to determine if they play a role in parturition. Reverse-transcriptase PCR revealed that specific Aqp mRNAs were detectable in the myometrium of nonpregnant and late-pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…The present experiments showed that OT increased AQP1 mRNA expression after 24-h and decreased AQP5 mRNA after 3 and 24 h incubation, but had no effect on AQP1 or AQP5 protein content. These results partially are in agreement with the data obtained very recently by Ducza et al (2014). They indicated that OT treatment increased AQP2 mRNA levels but also specifically reduced the expression of AQP5 in the rat uterus on Day 18 of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present experiments showed that OT increased AQP1 mRNA expression after 24-h and decreased AQP5 mRNA after 3 and 24 h incubation, but had no effect on AQP1 or AQP5 protein content. These results partially are in agreement with the data obtained very recently by Ducza et al (2014). They indicated that OT treatment increased AQP2 mRNA levels but also specifically reduced the expression of AQP5 in the rat uterus on Day 18 of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we can hypothesize that regulation of AQPs expression seemed to occur at the post-transcriptional level as protein expression upon Western-blot was pronounced. Further, those inverse relations are not accidental, they also happened in other studies performed by Klein et al (2013) and Ducza et al (2014). Therefore, it is not clear how tightly transcription and translation are correlated during such development processes.…”
Section: Discussionmentioning
confidence: 81%
“…In our earlier studies, it was determined that AQP5 expression shows the highest value on day 18 of pregnancy, and a remarkable decrease was found on the last day of pregnancy in rats [22]. …”
Section: Discussionmentioning
confidence: 99%
“…The presence of a copulation plug or the presence of sperm in the native vaginal smear was accepted as proof of the mating. These female animals were separated and regarded as first-day pregnant rats [22,35]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation